(untitled) (Research, Society and Development, 2020)
Violence against women is a social problem related to historical issues of inequality of power between men and women, whose deconstruction and containment face the reluctance of cultural practices and knowledge that hinder the application and effectiveness of laws protecting women. This work aims to study the virtual violence committed against women in Belém / Pará, in the years 2016 to 2018, through the analysis of police reports registered by female victims in the Civil Police’s Prevention and Repression against Technological Crimes Division, as well as in the other police stations in the city. For data analysis the statistical technique of descriptive data was used. The results show that there is an increase in violence against women in Belém, however, in cyberspace this rate is more accelerated. There is also a predominance of patrimonial violence as the damage most inflicted on victims. The conclusions of this research allow us to state (a) that violence against women in Belém does not reflect the national profile of studies in which physical violence comes first; (b) patrimonial violence prevails in cyberspace, where women from social classes C and D, from "central" neighborhoods represent the majority of victims.